Flood recession agriculture for food security in Northern Ghana: Literature review on extent, challenges, and opportunities - Sidibe, Yoro; Williams, Timothy O.; Kolavalli, Shashidhara (International Food Policy Research Institute, 2016)
This review describes a range of physical and socio-economic scientific methods and field activities that will be implemented in a proposed research project to develop a better understanding of the extent and patterns of flooding and the potential of flood-recession agriculture. These activities will allow the hydrological characteristics of the river to be matched to crop-livestock systems of flood recession agriculture that are well suited to the study communities and their organizational and institutional frameworks in order to support sustainable growth of such systems. This detailed study will provide recommendations on the technical, economic, institutional and policy measures needed to achieve sustainable intensification of flood recession agriculture in northern Ghana, while complementing efforts undertaken to promote other types of water management systems. Options for out-scaling of flood recession agriculture beyond the study area to other suitable areas will also be explored. The expectation is that the proposed project will improve food security by enhancing knowledge on effective flood recession practices, enhance rural incomes through expanded dry-season farming with new opportunities for rural employment, and improve adaptation to climate change by building more resilient farming communities. To achieve these expected outcomes, proactive policies that clearly identify flood recession agriculture as an alternative farming practice and provide institutional mandates to irrigation support services to promote it through training, demonstration, and outreach programs will be equally valuable.